The Rules of Forensic Medicine Examination in Diagnosis of Electrical injury in Childhood - Aghakhani, K; Mehrpisheh, Sh; Memarian, A; Shakeri, M (International Journal of Medical Toxicology and Forensic Medicine, 2013)
<!–[if gte mso 9]> <![endif]–> Background: History taking is a duty that must get out in different situation as child’s parents or in adults by themselves, to able provide the best helps in minimum time. Certainly, the information come out from history have significant effects on management plans. Case Presentation: A 16 months baby that transfers to ER department with complete cardiorespiratory arrest and after response to resuscitation the medical management was done for him. As history taking, he found unconsciousness near dress pan with wet dressing in bathroom. In physical exam the little impact traumatism on his/her head and face was detected. In blood and urine samples, there were not significant findings for toxicological screening. The physician requested for forensic specialist consultation for ruling out any child abuse doubt. The future examination was done by forensic team and they found the hyperkeratotic nodules on palmar surface of first phalange of right index finger due to electrocution. Conclusion: The history taking and following physical exam have greatest significant moment and the detailed and exact physical examination include whole parts of body, especially in children who couldn’t present and complain about their problems completely.